ANALISIS PENINGKATAN MUTU PENDIDIKAN MADRASAH IBTIDAIYAH MUHAMMADIYAH TEDUNAN KECAMATAN GRINGSING, BATANG, JAWA TENGAH: ANALISIS PENINGKATAN MUTU PENDIDIKAN MADRASAH IBTIDAIYAH MUHAMMADIYAH TEDUNAN KECAMATAN GRINGSING, BATANG, JAWA TENGAH - Hadi Marzuki (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI), 2024)
This study aims to examine the influence of internal control implementation and quality culture on the perception of educational quality improvement at MI Muhammadiyah Tedunan, Gringsing Sub-district, Batang, Central Java. The research involved 44 respondents and was conducted through a survey approach using questionnaires. A quantitative approach was employed, utilizing multiple linear regression analysis. The study underwent validity, reliability, and classic assumption tests. The results indicate that the implementation of internal quality assurance significantly influences the perception of educational quality improvement. Additionally, quality culture also influences the perception of educational quality improvement. The implications of this research can serve as a foundation for MI Muhammadiyah Tedunan and similar educational institutions to continuously enhance the implementation of internal quality assurance and strengthen quality culture to achieve better educational quality.